Effect of vitamin D supplementation to prevent acute respiratory tract infection : an evidence-based case report - Oki Yonatan Oentiono; Nurul Ratna Mutu Manikam (World Nutrition Journal, 2020)
Background: One of the frequent health problems that regularly occurs in Indonesia, as a tropical country is an acute respiratory tract infection, including influenza. Since immunological benefit of vitamin D already proven, hypothetically, vitamin D can be used as protective agent to prevent influenza or other respiratory tract infections. Objective: This evidence-based case report was focused on the evaluation of protective ability of vitamin D supplementation to prevent influenza or other acute respiratory tract infections.Methods: Literature searching was conducted on PubMed data base and Cochrane Library using the related keyword combinations.Results: Two randomized-clinical trials (RCTs) and a meta-analysis study were fulfilled the eligibility criteria. Vitamin D supplementation did not reduce the incidence of influenza but reduce the incidence of non-influenza infection. High-dose vitamin D supplementation had no effect on the reduction of acute respiratory tract infection incidence. The meta-analysis concluded that vitamin D supplementation reduced the risk for acute respiratory tract infection and the stronger effects occurred on low-levels of vitamin D serum.Conclusion: Vitamin D supplementation may prevent acute respiratory tract infections, especially in subjects with low-levels of vitamin D serum.